English for academic correspondence and socializing - Wallwork, Adrian; SpringerLink (Online service). (Boston, MA Springer US, 2011)
English for Academic Correspondence and Socializing is the first ever book of its kind specifically written for researchers of all disciplines whose first language is not English. With easy-to-follow rules and tips, and with authentic examples taken from real emails, referee's reports and cover letters, you will learn how to:use strategies for understanding native speakers of English; significantly improve your listening skills; organize one-to-one meetings; feel confident at social events; manage and participate in a successful conversation; write effective emails; review other people's manuscripts - formally and informally; reply effectively and constructively to referees' reports; write cover letters to editors; use the telephone and Skype; participate in (video) conference calls; exploit standard English phrases Other books in the series: English for Presentations at International Conferences English for Writing Research Papers English for Research: Usage, Style, and Grammar English for Academic Research: Grammar Exercises English for Academic Research: Vocabulary Exercises English for Academic Research: Writing Exercises
Electronic reproduction.
Keywords: English language -- Usage -- Handbooks, manuals, etc; Language and languages; Electronic books